Evaluation of apically extruded debris during root canal retreatment with several NiTi systems - Dincer, ASİYE NUR; DİNÇER, ASİYE NUR; Er, O.; CANAKCI, B. C. (My University, 2015)
AimTo compare the amount of debris extruded apically during root canal retreatment using ProTaper, Mtwo and Reciproc instruments with hand H-files.